Nanocompósitos aplicados à tecnologia de fertilizantes nitrogenados e fosfatados - Martins Junior, Alexandre Antonio Fidelis (Universidade Federal de São Carlos, 2026)
The growing demand for food, driven by population growth, has required modern agriculture to achieve higher levels of productivity. Fertilizers play a fundamental role in this context; however, conventional products exhibit low agronomic efficiency, with significant nutrient losses due to volatilization, leaching, and fixation in the soil. In response to these challenges, nanotechnology has emerged as a promising strategy for developing controlled-release fertilizers capable of synchronizing nutrient availability with plant demand. Among the various nanotechnological approaches, two complementary strategies have attracted particular attention: the production of extruded urea–montmorillonite nanocomposites and the development of thin polyurethane coatings incorporating lamellar materials for urea granules. Among these lamellar materials, montmorillonite exhibits a high cation exchange capacity, effectively retaining ammonium ions and reducing ammonia volatilization, whereas hydrotalcite, owing to its anion exchange properties, can regulate phosphate diffusion and delay its immobilization in the soil. Extruded urea–montmorillonite nanocomposites exhibited sustained nutrient release for up to 120 hours in water, with urea intercalation between the clay layers confirmed by X-ray diffraction. Polyurethane coatings containing less than 5 wt.% lamellar materials effectively controlled nitrogen and phosphorus release, reducing nutrient losses through volatilization and soil fixation while achieving performance comparable to or better than that of thicker commercial coatings. Overall, nanotechnology applied to fertilizers, particularly through the incorporation of lamellar materials into polymer matrices or extruded composites, represents a viable, cost-effective approach with significant environmental benefits for improving fertilization efficiency and mitigating the impacts associated with intensive agriculture.
Nanocomposites applied to nitrogen and phosphate fertilizer technology
Keywords: Nanotecnologia; Fertilizantes; Liberação controlada; Montmorilonita; Hidrotalcita; Nanocompósitos; Revestimentos poliméricos; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA::ANALISE DE TRACOS E QUIMICA AMBIENTAL; 2. Fome Zero e Agricultura Sustentável; 6. Água Potável e Saneamento